ANALISIS MOTIVASI BELAJAR MATEMATIKA SISWA MAN 1 KOTA CIREBON PADA PEMBELAJARAN DARING DIMASA PANDEMI COVID-19 - Azizah Azizah; Putik Rustika; Desy Lusiyana (Jurnal Edukasi dan Sains Matematika (JES-MAT), 2022)
This study aims to determine the students' motivation to learn mathematics in online learning during the covid-19 pandemic at MAN 1 Cirebon City in class XI. This type of research is a field research with a descriptive qualitative approach. Methods of data collection is done by observation, questionnaires, interviews and documentation. Researchers took high school students at MAN 1 Cirebon City class XI as a sample, data source sample collection was done purposively and snowball to produce a sample that can logically be considered representative of the population and find key informants who have a lot of information. The results of the study stated that the mathematics learning motivation of MAN 1 Cirebon City students during the covid-19 pandemic was in the "moderate" category with the average percentage gain from the observational analysis of learning motivation of 56.25%, while the results of the questionnaire analysis of learning motivation obtained an average percentage by 78.42% so that it is included in the "high" category. Based the results of interviews and questionnaires, can be concluded that students of MAN 1 Cirebon City have high motivation. So, the motivation for learning mathematics at MAN 1 Cirebon City students in online learning during the COVID-19 pandemic is categorized as "high" from the results of interviews where students meet six indicators of learning motivation.